A Study of Relationship Between International Performance and ESG Rating of Pharmaceutical Companies in India (The Journal of Theoretical Accounting Research, 2026)
This study examines how international performance shapes sustainability accounting outcomes in Indian pharmaceutical companies by conceptualizing ESG ratings as proxies for firms’ sustainability accounting practices. Drawing on stakeholder theory, legitimacy theory, and institutional theory, the study explains how international exposure alters disclosure pressures and legitimacy demands, thereby influencing ESG accounting dimensions differently. Using CRISIL ESG ratings for 45 Indian pharmaceutical companies for March 2025, the study empirically tests theory-driven propositions linking export intensity, international market reach, and geographic dispersion of operations to ESG, environmental, social, and governance accounting outcomes. The findings indicate that international performance is significantly associated with overall ESG ratings and environmental accounting outcomes, while social and governance dimensions remain largely unaffected. These results suggest that environmental accounting practices are more responsive to transnational legitimacy pressures, whereas social and governance accounting practices remain institutionally embedded within the domestic regulatory context. By positioning ESG ratings as secondary sustainability accounting information systems, this study advances sustainability accounting theory by explaining how internationalization reshapes disclosure in emerging-market firms beyond financial performance considerations.